Enabling immune checkpoint blockade efficacy in T-lymphopenia by restoring CD8 T cell dynamics with IL-7 cytokine therapy - Kang, Yeon-Woo; Choi, Donghoon; Moon, Dain; Lee, Kun-Joo; Oh, Youngsik; Yang, Jaehyuk; Jeong, Siheon; Park, Uni; Im, Sun-Kyoung; Yang, Se Hwan; Lee, Seung-Woo (Frontiers in Immunology, 2024)
IntroductionT-lymphopenia (TLP) is a frequently observed condition in cancer patients, often exacerbated by conventional chemo/radiotherapy, which impairs the efficacy of subsequent immune checkpoint blockade (ICB) therapy. This study aimed to understand the impact of TLP on ICB responsiveness and explore potential therapeutic strategies to enhance antitumor immunity.MethodsTo investigate ICB responsiveness depending on the severity of TLP, first, we established TLP mouse models that mimic clinically observed mild and severe TLP through thymectomy and anti-Thy1-induced peripheral T cell depletion. T cell-replete mice and T-lymphopenic mice were inoculated with palpable or advanced tumors to evaluate the antitumor efficacy of anti-PD-1 therapy according to the severity of TLP. Additionally, by utilizing established murine models, we analyzed matched blood, tumor-draining lymph nodes (TDLNs), and tumor samples by flow cytometry to investigate the mechanisms by which ICB responsiveness is impaired under T-lymphopenic conditions. Finally, to evaluate the combination effect of anti-PD-1 and recombinant IL-7 cytokine therapy (rhIL-7-hyFc) in T-lymphopenic conditions, we administered anti-PD-1, rhIL-7-hyFc, or both to advanced tumor-bearing T-lymphopenic mice and subsequently analyzed tumor growth and survival rates.ResultsUsing mouse models mimicking clinical TLP, we observed that the antitumor efficacy of anti-PD-1 therapy was severely impaired in TLP, depending on the degree of TLP and the immunogenicity of the tumors. TLP mice showed a significant reduction in systemic CD8 T cells but stable intratumoral CD8 T cell numbers, suggesting maintained tumor infiltration despite systemic downregulation. Crucially, TLP led to a shift in the composition of tumor-infiltrating lymphocytes, with a decrease in PD-1+ tumor-reactive CD8 T cells and an increase in PD-1− bystander cells. This reduction in PD-1+ cells was linked to impaired clonal expansion in tumor-draining lymph nodes. To counteract these effects, we introduced recombinant IL-7 cytokine therapy (rhIL-7-hyFc), which effectively restored systemic T cell counts, enhanced PD-1+ CD8 T cell proliferation within tumors, and increased the population of stem-like progenitor cells. The combination of rhIL-7-hyFc and anti-PD-1 therapy resulted in significant tumor regression and improved mouse survival.DiscussionOur findings highlight the critical role of IL-7 in reshaping the CD8 T cell landscape to improve ICB efficacy in TLP conditions, proposing a sequential therapeutic approach: conventional therapy to reduce tumor burden and enhance immunogenicity, followed by IL-7 therapy to restore and rejuvenate CD8 T cells, culminating in effective ICB treatment.